2018
DOI: 10.3390/nano8030169
|View full text |Cite
|
Sign up to set email alerts
|

Strongly Iridescent Hybrid Photonic Sensors Based on Self-Assembled Nanoparticles for Hazardous Solvent Detection

Abstract: Facile detection and the identification of hazardous organic solvents are essential for ensuring global safety and avoiding harm to the environment caused by industrial wastes. Here, we present a simple method for the fabrication of silver-coated monodisperse polystyrene nanoparticle photonic structures that are embedded into a polydimethylsiloxane (PDMS) matrix. These hybrid materials exhibit a strong green iridescence with a reflectance peak at 550 nm that originates from the close-packed arrangement of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…where m is the order of a diffraction maximum, λ is the wavelength of the reflectance maximum, d 111 is the interplanar distance between crystallographic (111) planes, n eff is the effec- tive refractive index of the CCA, n air is the refractive index of the medium (in our case air) from which light falls in and θ is the incidence angle [8,9,36]. The incidence angle was varied from 8° to 65° in the experiments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…where m is the order of a diffraction maximum, λ is the wavelength of the reflectance maximum, d 111 is the interplanar distance between crystallographic (111) planes, n eff is the effec- tive refractive index of the CCA, n air is the refractive index of the medium (in our case air) from which light falls in and θ is the incidence angle [8,9,36]. The incidence angle was varied from 8° to 65° in the experiments.…”
Section: Resultsmentioning
confidence: 99%
“…Photonic crystals (PhCs) used for chemical sensors can be divided into three groups depending upon their structure, that is, one-dimensional (1D), two-dimensional (2D), and three-dimen-sional (3D) [1][2][3][4][5][6][7][8][9][10]. 2D and 3D structures used as chemical sensors are studied in most projects.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although PSCs have a fairly simple device architecture, several key aspects such as the formation of flat and uniform interfaces or phase separation in the active layer can considerably influence their photovoltaic characteristics. Unlike spin-coating during which the thin films are rapidly formed owing to centrifugal forces, push-coating is a two-step process in which the solution quickly spreads laterally through capillary forces, followed by solvent diffusion into PDMS in the vertical direction (Figure ). In our previous attempts to fabricated PC films for functional optoelectronic devices, we selected relatively long push-coating times to ensure that all the solvent diffused into PDMS before its removal. , However, previous studies on PDMS also suggest that small volumes (<5 μL) of chlorinated solvents such as DCB should diffuse relatively rapidly into PDMS. , In fact, when push-coating 3 μL of PCDTBT:PC 71 BM solution in DCB onto a ZnO-coated glass substrate, we found that over 90% of the solvent has already diffused into PDMS after 1 min (Table S1). On the other hand, the amount of DCB remaining in the PCDTBT:PC 71 BM is lower than 3% of the deposited solvent volume (lower than 0.08 μL).…”
Section: Results and Discussionmentioning
confidence: 99%